2015
DOI: 10.1111/ans.13171
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node grafting in the treatment of upper limb lymphoedema: a clinical trial

Abstract: We conclude that this is a safe procedure and should be further investigated as an alternative to a microsurgical procedure as a treatment for upper limb lymphoedema. Further research with a larger sample size is needed to confirm the findings of this pilot study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
0
11
0
1
Order By: Relevance
“…35,41 The 12 high-quality LVA studies had a mean AE SD MINORS score of 13.9 AE 1.2. [42][43][44][45] Thus, only patients with persistent swelling received VLNT. Seven studies reported complications of VLNT procedures.…”
Section: Lymphatic Reconstructive Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…35,41 The 12 high-quality LVA studies had a mean AE SD MINORS score of 13.9 AE 1.2. [42][43][44][45] Thus, only patients with persistent swelling received VLNT. Seven studies reported complications of VLNT procedures.…”
Section: Lymphatic Reconstructive Proceduresmentioning
confidence: 99%
“…Seven studies reported complications of VLNT procedures. [42][43][44][45][46][47][48] The most common complications were cellulitis, lymphocele, and donor site pain, seroma, and lymphedema. Other complications included hematoma, wound dehiscence, wound infection, hydrocele, partial skin graft loss, and venous congestion.…”
Section: Lymphatic Reconstructive Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…In this edition of the journal, Travis et al have added another procedure to this mix in the form of lymph node grafting. 1 In a small number of cases, they have reported the transfer of lymph nodes into lymphoedematous limbs without microanastomosis of the feeding vessels. Preliminary evidence indicates reduction in limb volumes and some restoration of lymphatic flow.…”
mentioning
confidence: 99%